Microbiota-derived bile acid metabolic enzymes and their impacts on host health - Haohan Ma; Kai Wang; Changtao Jiang (Cell Insight)
Bile acids are amphipathic sterol molecules regulated by both the host and gut microbiota, serving as classical mediators for deciphering host-microbiota interactions. Synthesized primarily in the liver and undergoing extensive structural modifications along the gastrointestinal tract, bile acids are dynamically shaped by diverse bile acid metabolic enzymes, especially from gut microbiota. Beyond their canonical detergent-like functions, bile acids act as receptor modulators, immune regulators, and microbiota sculptors, profoundly involved in regulating host metabolic processes, maintaining immune homeostasis, and contributing to metabolic disorders when dysregulated. The modifications of bile acids by microbial enzymes critically influence their functional diversity. However, despite the vast array of bile acid modifications observed, significant gaps remain in the systematic identification and characterization of microbial bile acid metabolic enzymes. This review underscores the urgency of exploring the biosynthetic pathways for the production of key bile acids and highlights its potential to advance precision therapeutic strategies targeting gut microbiota and their enzymatic machinery.